PERTANGGUNG JAWABAN PELAKU BINARY OPTION TERHADAP HUKUM POSITIF DI INDONESIA - Ferdiansyah M. A; Frans Simangunsong (Gapenas Publisher, 2022)
Binary Option Trading has become quite a topic of public discussion lately, because there are many influencers and advertisements scattered about the huge profits that can be obtained through Binary Option Trading, so many people are tempted to try to enter it without understanding what and how the Binary Option system is. alone. In addition, the legality of Binary Option Trading in Indonesia is still questionable. Regarding the types of commodities included in the subject of futures contracts, it is regulated in CoFTRA Regulation No. 3 of 2019 concerning Commodities, Binary Options are not included in the subject written in Article 1. This can indirectly mean that Binary Options are illegal. The most recent case is a binary option scheme which is defined as a gambling practice. Gambling activities are prohibited by Article 303 of the Criminal Code (KUHP), Law (UU) Number 7/1974, as well as Government Regulation Number 9/1981, and Law Number 11/2008 (UU ITE). So the question arises, is there an alternative civil law regulation for victims of binary options trading cases? What is the perpetrator's responsibility for binary options under the guise of online investment? In this study, the researcher uses normative legal research, namely research that is useful for finding and answering legal issues, the rule of law, legal principles or legal doctrines encountered from a normative perspective and to find out whether the rule of law is in accordance with legal norms. . This normative law research is used to solve the problem of the legal issues faced by only examining the legal norms. So from research with normative legal methods will produce appropriate prescriptions and should be according to law.